Understanding business strategy factors that support or impede moving business capabilities to a cloud environment - Davids, Faghmie Jamiel (Department of Information Systems, 2018)
Organisations are facing increased competition in contemporary business environments. At the same time, cloud computing is a catalyst for new software applications and services available to organisations. Therefore, cloud computing is a viable option to provide innovation within the organisation. Therefore, organisations need to recognise the potential transformation of its business model, to take advantage of cloud computing. This research sets out to describe and explain the relationship between the various business strategy factors and CC. Organisations have to guard against using cloud-computing capabilities only to provide organisational efficiencies, as the efficiencies gained do not always translate into business value. Adopting cloud computing can cause disruptions in the organisation. Therefore, the organisation needs a strategy and understand the relationship between the business strategy and the cloud computing options available. The present study performs multi-method qualitative research, within the South African context. By taking a constructivist view, the researcher believes the knowledge will emerge from the interaction the people have with their environment. The research purpose states the research as descriptive and explanatory. Data collection for the present study performs face-to-face interviews. A general interview-guided approach ensures the research covers same areas of interest in all the interviews. For the data analysis, the researcher uses an inductive thematic analysis method. Software-as-a-Service influences the customer behaviour and forces organisations to re-evaluate their use of cloud computing. However, new cloud computing capabilities brought into the organisation need to provide a value proposition with an expected time-to-market. Also, large organisations require a technology architecture review to assess the impact on their infrastructure. The multi-faceted cost structure coupled with legacy systems and legacy investment products can prevent the adoption of cloud computing. Another factor is the vendor relationship and their influence regarding the solutions into which an organisation invests. The present study concludes how cloud computing offers no competitive differentiation for South African investment services organisations. For these organisations, their existing business models remains profitable. Business strategy, therefore, has no compelling reason to consider cloud computing. Furthermore, information technology is a utility service. For these organisations, the information technology and business strategy align through the service-level method. This alignment method forces the information technology department to focus on maintaining a stable and reliable infrastructure. Cloud computing is only considered when contributing to the service-level. A misalignment then follows, and individual business units adopt cloud computing to fulfil their business need. As a result, the business unit is ready to adopt cloud computing while the information technology department is a hindrance towards adopting cloud computing. Software-as-a-Service solutions are the most used cloud computing option, based on its ability to offer an accelerated time-to-market for proof-of-concept products and services. However, most final business solutions move onto the internal infrastructure of the organisation. Platform-as-a-Service and Infrastructure-as-a-Service are used to a lesser degree by organisations in this study.